Mathematical games: stimulating the wellbeing and encouraging older adults learning - Rocha, Eridan Pires Conde; Abdala, Rachel Duarte (Revista Hipótese, 2018)
The games are methodological strategies for teaching used often in the schools with the purpose of dynamizing the teaching and the learning. Also the games can provide moments of happiness in the students. In the learning of older adults, games are also efficient because of their playful and consequently stimulating the well-being. This study has as scope of analysis the application of the project Mathematical Games for Older Adults, held in 2015 in an academic institution. In the scope of university extension, this project constitutes as a work experience, whose objective was to stimulate the memory and to stimulate the learning, increasing the wellbeing. It is a proposal also had the intention of collaborating for the activation and performance of the learning in the old age, bosting the social relations and the feeling of happiness of the participants. This experiment was carried out in weekly two-hour meetings in which mathematical games were applied to a group of older people in a nursing home care in the city of Campos do Jordão, SP. Through the observations and reports of participants, the impact of such experience on the development of cognitive abilities, functional and instrumental activities of the daily life of the elderly was analyzed. At the end of this study, it was observed that experiences with games among the elderly can be triggering new pedagogical strategies focused on the elderly adult, as well as experiences that stimulate the construction of information using mathematics.